Measuring scope efficiency for crop and beef farms - Langemeier, Michael R.; Jones, R.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study evaluated scope efficiency (the degree of efficiency gained from producing more than one product within the same farm) for a sample of crop and beef farms in Kansas. Scope and economic efficiency were estimated for each individual farm. Average scope efficiency was 0.25, indicating that joint production of crop and beef enterprises on the same farm reduced cost approximately 25%. Scope efficiency was significantly higher for smaller farms. Despite the relatively higher scope efficiency levels, economic efficiency (relative cost efficiency) was significantly lower for smaller farms. Economic efficiency is related to cost control and economies of size, which are both positively related to farm size.
Keywords: Beef; Scope efficiency; Crop and beef farms